2020
DOI: 10.3390/nu12103161
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Associations with Serum Bone Turnover Markers

Abstract: Bone is a dynamic tissue that is in a constant state of remodeling. Bone turnover markers (BTMs), procollagen type I N-terminal propeptide (P1NP) and C-terminal telopeptides of type I collagen (CTX), provide sensitive measures of bone formation and resorption, respectively. This study used ultra-high-resolution metabolomics (HRM) to determine plasma metabolic pathways and targeted metabolites related to the markers of bone resorption and formation in adults. This cross-sectional clinical study included 34 adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…We observed that females had greater biomarkers of bone resorption (CTX1 and CTX/P1NP) than males. In a study investigating healthy young adult serum using metabolomics and biomarker analysis CTX1 was positively correlated with lipid metabolism (fatty acid biosynthesis), beta oxidation, and carbohydrate metabolism in humans (66) . Previous studies found that osteoclasts' high energy demand can be fueled by lipids (66,(79)(80)(81) , but it is uncertain if osteoblasts and osteocytes are fueled by lipids in the same way.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed that females had greater biomarkers of bone resorption (CTX1 and CTX/P1NP) than males. In a study investigating healthy young adult serum using metabolomics and biomarker analysis CTX1 was positively correlated with lipid metabolism (fatty acid biosynthesis), beta oxidation, and carbohydrate metabolism in humans (66) . Previous studies found that osteoclasts' high energy demand can be fueled by lipids (66,(79)(80)(81) , but it is uncertain if osteoblasts and osteocytes are fueled by lipids in the same way.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms of tryptophan prominently affecting bone remodeling is through stimulating proliferation and differentiation of osteoblasts and bone marrow mesenchymal stem cells (87) . In both humans and mice, tryptophan has been associated with osteoclast activity and was positively associated with CTX1 levels (66) . In our study, there was a moderate correlation between bone strength and CTX1/P1NP for males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A plasma metabolomics study involving 34 adult women found that the serum C-terminal telopeptide (CTX) concentration, an index of bone resorption, was related to lipid and fatty acid metabolism pathways, but not carbohydrate metabolism. Osteoclasts in the active bone resorption state show a high capacity for fatty acid β oxidation, suggesting that the high energy state of active osteoclasts may be mainly supported by lipid catabolism ( 127 ). Short-chain fatty acids (SCFAs) inhibit osteoclast production in vivo and in vitro ( 128 ).…”
Section: Other Substrates For Energy Metabolismmentioning
confidence: 99%
“…The crosslinking process of bone collagen is essential for bone substation formation and is considered important in bone reconstruction [ 90 ] and fracture healing. Bone conversion markers, type I pre-collagen N-end peptides and type I collagen C-end peptides, such as provide sensitive indicators of bone formation and bone absorption, respectively [ 92 ]. Metabolomics-based studies have reported correlations found with amino acid and bone health assessments [ 93 95 ].…”
Section: Energy Metabolism (Glucose Amino Acid and Fat) In Bonementioning
confidence: 99%